“Emi lokan, Yoruba lokan”: expression of ideologies in Bola Tinubu’s political speech - Matthew Ige (Hasanuddin University, 2023)
Beyond the traditional import of language which is for communicative purpose and information sharing, its usefulness cuts across other strands such as for expression of one ideology or others, representation and identification of self and other social groups among others, especially within the political context. Previous linguistic studies on political discourse with emphasis on (intra party) electioneering campaign speeches have invested on the nexus between language and politics. Such studies, however, have not exteriorised expressions of ideologies in Emi lokan, Yoruba lokan campaign slogan of Bola Tinubu in the build-up to 2023 Nigeria’s presidential election. This study, consequently, studies the differing ideologies expressed in the Emi lokan, Yoruba lokan speech made by the All Progressive Congress’ presidential aspirant in the build-to the party’s 2023 presidential primary election. The data for the study is audio-visual of the speech obtained from the YouTube platform, which was rendered in the mixture of English and Yoruba languages, given the nature of the audience where the speech was made. The translated video was transcribed into MS Word. The selected excerpts were subjected to Critical Discourse Analysis, borrowing insight from van Dijk’s (2006) socio-cognitive model. The findings reveal that supremacist, collectivist, welfarist and ethnocentric ideologies are embedded in Bola Tinubu’s emi lokan slogan/speech which are indexed through certain discursive moves.